ANALISIS PENDAPATAN PETANI PENGOLAH KOPRA DI DESA PUSUNGI KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - kalai, Farida basir; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2018)
Copra is one of the processing coconut which cultivated by people in Indonesia. This commodity is generally used as a raw material for the manufacture of coconut oil is produced from the flesh of the coconut. Copra is a endoaperm of coconut which has been dried through a process of drying, the moisture content in endosperm about 50% was reduced to only 5-6%. Copra quality can be improved by performing storage the whole fruit in certain time before coconuts processed into copra. The purpose of this research is to know the revenue obtained in the processing of Copra Farmers in Pusungi Village Ampana Tete Sub-District Tojo Una-Una Regency. This research is determined by simple random method (simple random sampling) and Farmer copra populations as much as 102 people and the number of samples obtained as many as 31 respondents.The data used the primary and secondary data. Data analysis is an analysis of income used π = TR-TC. Production data is data processing of Copra in April-July 2016. The results of the analysis showed that the average income of farmers in Pusungi Village Ampana Tete Sub-District Tojo Una-Una Regency is Rp. 4,064,917. Income amounting to Rp. 4,064,917 retrieved from a reduction of between Rp. 9,393,947 reception with total cost amounting toRp. 5,329,030.